The quest for exploring the normal speed of handwriting in students of grade 2-5 in Tehran - Navid Mirzakhani; Atiyeh javan Tash; Zahra Pashazadeh (Shahid Beheshti University of Medical Sciences, 2012)
Background and Aim: Slow handwriting speed is one of the major problems encountered by school-aged children having handwriting difficulties. These children are often referred to occupational therapy for assessment and intervention. However, to date, no norms of handwriting speed have been published for the Iranian writing system for school-aged children. The purpose of this study was to document handwriting speed performance of Tehran children from Grades 2 to 5.Materials and Methods : Participants were 400 children from Grades 2 to 5 from 20 elementary schools in Tehran. Participants were asked to copy text that was printed at the top of page on the writing lines below with normal speed at 5 minutes .Then, the sheets were gathered and number of letters written, were calculated by Two raters . There for, Scores of 120 students rated as fast, normal or slow by their teachers were compared to examine the test's construct validityResults: Results showed that 50% of children were boys and 50% were girls. And 75% of children were studied in governmental schools and 25% of them were studied in nongovernmental schools. And 80% children were Right-handed and 20% were left-handed. Conclusion: Results showed that handwriting speed increased with age; and the rate of increase was found to be greatest among Grade 5. And handwriting speed assessment test has excellent inter-rater reliability (r=1, p=0.000) and construct validity (r=0/798, p=0.000).